Heavy metals Contamination in Soil and Water Samples in Omo Forest Reserve, Nigeria (African Journal of Biomedical Research, 2019)
The study examined heavy metal levels in soil and water samples and also determined the water quality parameters of water samples in Omo Forest Reserve. Water samples from River Omo (upper, middle and lower courses) and soil samples (at different locations in the reserve) were randomly collected for two seasons (one wet and one dry) and taken to the laboratories for heavy metal analyses and evaluation of water quality parameters using standard methods. Data collected were presented and expressed as Mean ± Standard Deviation and statistical significance was set at α0.05. The result showed that the soil samples had more heavy metal contamination during the wet season than the dry season with iron (Fe) having the highest mean concentration in the soil and water samples. Phosphate was not detected in the water samples during the dry season. The average values of sulphate (except dry season), phosphate, nitrate, chloride, alkali, TDS, TSS and TS observed from this study were below the WHO permissible limits. The high BOD values obtained from the study indicates heavy pollution of the river. Escherichia coli, Staphyloccocus aureus and fungi had no counts during the wet and dry season periods. The absence of Escherichia coli indicates no faecal contamination in the River. There is a great impact of anthropogenic activities on the ecosystem of the Omo Forest Reserve based on the concentration level of heavy metals investigated. There is need for government to explicitly curtail the high level of environment-degrading anthropogenic activities within and around the reserve.
Keywords: Heavy metals; Ecotoxicology; Water quality parameters; Omo Forest Reserve